Lifshitz Transitions Induced by Temperature and Surface Doping in Type-II Weyl Semimetal Candidate Td-WTe2 - Zhang, Qihang; Liu, Zhongkai; Sun, Yan; Yang, Haifeng; Jiang, Juan; Mo, Sung-Kwan; Hussain, Zahid; Qian, Xiaofeng; Fu, Liang; Yao, Shuhua; Lu, Minghui; Felser, Claudia; et al. (Physica Status Solidi-Rapid Research Letters, 2017)
Using high resolution angle-resolved photoemission spectroscopy, we systematically investigate the electronic structure of Td-WTe2, which has attracted substantial research attention due to its diverse and fascinating properties, especially the predicted type-II topological Weyl semimetal (TWS) phase. The observed significant lattice contraction and the fact that our ARPES measurements are well reproduced by our ab initio calculations under reduced lattice constants support the theoretical prediction of a type-II TWS phase in Td-WTe2 at temperatures below 10 K. We also investigate the evolution of the electronic structure of Td-WTe2 and realize two-stage Lifshitz transitions induced by temperature regulation and surface modification, respectively. Our results not only shed light on the understanding of the electronic structure of Td-WTe2, but also provide a promising method to manipulate the electronic structures and physical properties of the type-II TWS Td-XTe2.
CRIS-Team Scopus Importer:2022-04-14
Keywords: angle-resolved photoemission spectroscopy; band reconstruction; Lifshitz transition; type-II Weyl semimetal